Cognitive Development in Children With Language Impairment, and Correlation Between Language and Intelligence Development in Kindergarten Children With Developmental Delay. (January 2015) - Liao, Su-Fen; Liu, Jui-Ching; Hsu, Chun-Ling; Chang, Ming-Yuh; Chang, Tung-Ming; Cheng, Helen
We performed a retrospective review of 65 children with developmental delay. The male-to-female ratio was 2.25 : 1, and the mean age was 5.8 years; performance IQ was 94.8, verbal IQ was 83, and full-scale IQ was 87.4. Twenty-three (35%) children had normal language development, 13 (20%) had below average language development, and 29 (45%) had developmental language disorder. Performance IQ was significantly better than verbal IQ in all children ( P < .001), and there was no difference within the 3 language groups. The performance IQ ( P = .007) of children with developmental language disorder and specific language impairment was significantly lower than that of children with normal language development. Performance IQ was found to be correlated with language score ( r = .309, P = .012). The children with language impairment were associated with lower IQ scores. The discrepancy between performance IQ and verbal IQ persisted in children with developmental delay, not only in children with language disorder.